Prevalence and Risk Factors Associated with Gross Pulmonary Lesions in Slaughtered Pigs in Smallholder and Commercial Farms in Two Provinces in the Philippines - Alawneh, John I.; Parke, Christopher R.; Lapuz, Eduardo J.; David, Jose E.; Basinang, Voltaire G.; Baluyut, Augusto S.; Barnes, Tamsin S.; Villar, Edwin C.; Lopez, Minnie L.; Meers, Joanne; Blackall, Patrick J. (Frontiers in Veterinary Science, 2018)
A cross-sectional study of lungs from 1,887 randomly selected pigs from 471 farms from two provinces in the Philippines was carried out to: estimate the prevalence of gross pathological lesions, identify potential risk factors and spatial clustering associated with high lung or pleurisy score farms. Lungs from pigs were scored at slaughter. Interviews with the farm managers were conducted to collect information about farm management and biosecurity practices. Of lungs examined, 48% had a lung score above 6 (maximum was 55) and 22% showed pleurisy. When data were aggregated at the farm level, commercial farms were at higher risk of being high lung score farms and high pleurisy farms compared to smallholder farms (P<0.01). Variables that were associated with an increased risk of a farm being a high lung score farm included the presence of a market pen on the farm, not vaccinating against hog cholera and the presence of another piggery within 500m. Practicing “feedback” (feeding pig manure, viscera or aborted material to pigs), presence of another piggery within 500m, and allowing commercial livestock vehicles on farm were all associated with an increased risk of being a high pleurisy farm. Spatial analyses revealed a primary 9.6 km-radius cluster of 39 farms with high lung and pleurisy scores in the south-east of Bulacan province. High lung and pleurisy score farms could be targeted to improve on-farm disease control programmes to reduce the risk of respiratory diseases. Clusters of high scoring farms could be prioritised for further investigations or for coordinating intervention efforts.